The Application of Guided Inquiry Learning to The Ability of Critical Thinking and Cognitives Learning - Gustari, Titin (Proceedings of the 1st UR International Conference on Educational Sciences, 2017)
This study aims to determine the ability of critical thinking and biology learning outcomes through the application of guided inquiry learning This research is a classroom action research (PTK), with descriptive analysis. Subjects in this study were students of class X ATP 4 SMK Negeri Pertanian Pekanbaru which amounted to 28 students consisting of 23 male students and 5 female students. The result of data analysis of critical thinking ability of students obtained in the first cycle is 78% with category critical enough increase of 1% in cycle II to 80% with critical category. Results of data analysis and cognitive learning outcomes for the absorption of students before the PTK is 71.7%, after PTK 72.2%, then an increase of 0.5% before the PTK. Absorption of students in the second cycle of 73% occurred in increase of 0.8% of the cycle I. Student classical completeness before the PTK is 39%, after the PTK in the first cycle of 61%, then an increase of 22% from before the PTK, and Classical mastery in cycle II is 64%, then there is an increase of 3%. Based on the results of the study showed that the application of guided inquiry learning can improve the ability of critical thinking and cognitive learning outcomes of biology of class X students ATP 4 SMK Negeri Pertanian Pekanbaru